2019
DOI: 10.2478/hukin-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and Motor Performance Variables are Decisive Factors for the Selection of Junior National Female Volleyball Players

Abstract: This study examined whether anthropometric and fitness tests might successfully predict selection of young female volleyball players for a junior national team. Sixty four female players (age: 14.4 ± 0.5 y, body height: 1.76 ± 0.05 m, body mass: 63.9 ± 6.4 kg) underwent a selection procedure for the junior national team. Anthropometric data and speed and power test results were obtained and players were graded for their performance in a volleyball tournament. Selected players differed from the non-qualified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
23
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 32 publications
8
23
0
9
Order By: Relevance
“…. ., " which is in line with research indicating that body height and spike jump reach are the decisive factors for the selection of junior national female volleyball players (Tsoukos et al, 2019). Conversely, previous studies have shown that anthropometric data are inefficient for discriminating between successful and unsuccessful talent-identified junior volleyball players (Gabbett et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…. ., " which is in line with research indicating that body height and spike jump reach are the decisive factors for the selection of junior national female volleyball players (Tsoukos et al, 2019). Conversely, previous studies have shown that anthropometric data are inefficient for discriminating between successful and unsuccessful talent-identified junior volleyball players (Gabbett et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…A player who changes direction quickly and efficiently is not necessarily effective in the game, for example, in his/her reaction to a ball flying at high speed (Young, 2015). However, as in previous studies, there was no significant difference between selected and unselected players in test results based on planned change-of-direction (Gabbett et al, 2007;Tsoukos et al, 2019). Our findings support this thesis, and no significant difference in zigzag agility test results was reported between selected and non-selected players.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Manuscript to be reviewed from studies that focused on the selection of female players for the national junior volleyball team. The selected players had a significantly higher BH than the players who were not selected (Papadopoulou et al, 2019;Tsoukos et al, 2019). The BH results presented in scientific studies correspond with the values determined in our volleyball players from VG2 (aged 13+), unless the studies deal with players selected for representative purposes.…”
Section: Discussionsupporting
confidence: 78%
“…The hypothesis of maturational theory suggests that physical development is an important factor in sports in which advanced maturation promotes performance. Volleyball is one of those sports in which certain anthropometric characteristics combined with physical performances (e.g., strength, power, agility) are important requirements (Petroski et al, 2013;Tsoukos et al, 2019). When analysing height, we observed that the medallist athletes were taller compared to other teams ( Figure 2).…”
Section: Discussionmentioning
confidence: 70%